2014
DOI: 10.1111/ijcp.12450
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of patient satisfaction with fesoterodine in the treatment of overactive bladder: effects of additional educational material

Abstract: In an observational study, most overactive bladder patients were satisfied with fesoterodine treatment. Because of the small sample size, the study does not support or refute the hypothesis that adding the SAGA tool will improve patient satisfaction with treatment. The potential effect of additional educational material in treatment-naïve patients warrants further dedicated studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…As a result, CYP3A inhibitors may be needed to ensure tolterodine metabolism to 5‐HMT for OAB treatment . Comparative studies performed during clinical administration have demonstrated a satisfactory response to fesoterodine compared to tolterodine . Such competence of fesoterodine compared with other muscarinic drugs has led us to focus on its synthetic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, CYP3A inhibitors may be needed to ensure tolterodine metabolism to 5‐HMT for OAB treatment . Comparative studies performed during clinical administration have demonstrated a satisfactory response to fesoterodine compared to tolterodine . Such competence of fesoterodine compared with other muscarinic drugs has led us to focus on its synthetic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate patient perception of efficacy and overall treatment satisfaction, COMPOSUR uses the OAB-q-SF questionnaire, assessing system bother and HRQL, which has also been used in a previous real-world study [ 25 ]. Although treatment satisfaction is sometimes assessed with the single-question Treatment Satisfaction Visual Analog Scale [ 25 , 26 ], COMPOSUR uses the OAB-SAT-q to measure patient satisfaction with treatment, enabling greater assessment of not only satisfaction but also side effects, convenience, and preference. COMPOSUR will monitor patients over a 12-month period, with patient visits occurring slightly more frequently than a previous 12-month-long real-world study [ 25 ]; however, frequency of study visits is representative of usual practice for treating providers.…”
Section: Discussionmentioning
confidence: 99%
“…Various OAB treatments improve PROM such as PPBC at the group level, and the present NIS confirm this. While such improvements are routinely observed to occur concomitant with improvements of diary-based OAB symptoms in randomized controlled trials and NIS, 3,[14][15][16][17][18][19][20][21][22] other than the original validation study 8 apparently only one previous study (all based on tolterodine) has explored relationships between PPBC and OAB symptoms at the single-patient level and was limited to analysis of baseline values. 3 The present analyses confirm those findings and extends them to treatmentassociated improvements.…”
Section: Discussionmentioning
confidence: 99%
“…However, the PPBC is an ordinal variable, which should be reported as medians or distributions and analyzed by nonparametric tests. While this has been done in the original validation studies, 8 few other studies in the field have followed that example 3,15,18 . Despite being scientifically unsound, many studies have reported PPBC as means, for instance, 19,21,22 which ignores that PPBC is an ordinal variable.…”
Section: Discussionmentioning
confidence: 99%